The Availability of Lower Level Implementers in the Implementation of the Free Nutritious Meals Program on Primary School in Klaten Regency - Winduro, Wirid; Wirawan, Riska (Indonesian Journal of Contemporary Multidisciplinary Research, 2025)
This study aims to analyze the preparedness availability of lower level implementers in executing the Free Nutritious Meals Program in primary schools in Klaten Regency. Although the program has not been officially delivered from government, strong indications suggest its likely implementation farther. The main focus of this research is to identify factors influencing implementers' readiness, challenges encountered, and the support needed to ensure the program's effective execution. A qualitative research approach was employed, utilizing data collection techniques such as interviews, simulation observations, and document analysis. The findings indicate that the level of preparedness availability among lower-level implementers remains deficient. This deficiency is influenced by several key factors, including the absence of local government support through socialization, inadequate resource availability, the implementers' capacity and competence, and community participation. Despite the program's planned nature, potential obstacles were identified, including limited facilities, unequal distribution of food supplies, and insufficient technical training for implementers. Furthermore, enhancing community participation is imperative to optimize the quality and sustainability of the program in select schools.